Relations Between Finland and North Korea - Saukkonen, Laura (My University, 2025)
The topic of this thesis is relations between Finland and North Korea. The scope of study is the period in Finnish – North Korean relations in the aftermath Korean War until establishment of North Korean trade representation in Helsinki in 1971. Through historical research on Finnish Ministry for Foreign Affairs archival material, this study attempts to shed light to questions such as what issues led to delaying the establishment of North Korean trade representation in Helsinki for almost a decade and what impressions officials of Finnish Ministry of Foreign Affairs had about North Korean motives on establishment of the trade relations. It seems that Finland’s concerns on maintaining. Neutrality policy played a central role in Finnish foreign policy in the aftermath of World War II and it seems that balancing between superpowers and pacifying eastern neighbour Soviet Union provided context for and played its part in development of relations with North Korea. In forming her approach to the divided Korea, Finland seemed to look also at its relations with divided Germany as a kind of a model. Finnish officials placed heavy emphasis on concrete trade in development of relations with North Korea, in order to avoid weakening the credibility of neutrality policy through accusations of growing political relations specific one side. Lack of concrete trade, suspicions of North Korean political motives above economical ones and potential negative consequences of weakened credibility of neutrality seemed to be some of the reasons that led to decade long talks of establishment of North Korean trade representation in Helsinki.
Keywords: Finland, North Korea, Neutrality policy, Historical research, Archival research